The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fpsyt.2020.00100
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Telomere Length Is Related to Brain Parenchymal Fraction and Attention/Speed in the Elderly: Results of the Austrian Stroke Prevention Study

Abstract: There are controversial results if leukocyte telomere length (LTL) is related to structural brain changes and cognitive decline in aging. Here, we investigated the association between LTL and 1) global MRI correlates of brain aging such as brain parenchymal fraction (BPF) and white matter hyperintensities (WMH) load and Fazekas score as well as 2) global (g-factor) and domain-specific cognition such as attention/speed, conceptualization, memory, and visuopractical skills. In total, 909 participants of the Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 27 publications
(35 reference statements)
3
28
1
Order By: Relevance
“…They also provided evidence that suggests non-replicative neurons involved in the age-related telomere erosion procedure detected in the brain [ 158 ]. However, there are controversial reports describing leukocyte telomere length (LTL) associated with structural alterations to the brain and decreased cognitive capacity during aging [ 159 , 160 ].…”
Section: Telomere and Brain Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…They also provided evidence that suggests non-replicative neurons involved in the age-related telomere erosion procedure detected in the brain [ 158 ]. However, there are controversial reports describing leukocyte telomere length (LTL) associated with structural alterations to the brain and decreased cognitive capacity during aging [ 159 , 160 ].…”
Section: Telomere and Brain Agingmentioning
confidence: 99%
“…Gampawar et al reported a highly unique link between LTL and brain parenchymal fraction (BPF) in the elderly. Also, they found that Longer LTL is connected with a larger brain and with better cognitive functioning in the attention/speed mediated by BPF [ 159 ]. In another study by Puhlmann et al, short-term LTL change was connected with structural brain alteration [ 160 ].…”
Section: Telomere and Brain Agingmentioning
confidence: 99%
“…The correlation between LTL and telomere dynamics in the central nervous system has been largely debated, but there is agreement in that TL in whole blood correlates with TL in most other tissues, including the brain [88]. While it is recognized that important differences exist in telomere biology and length in the different tissues of the human body, several studies suggest that LTL is significantly correlated with region-specific and total brain volume [89]. Interestingly, it has been suggested that shorter LTL is significantly associated with reduced size of the hippocampus [90].…”
Section: Discussionmentioning
confidence: 99%
“…11 Recent meta-analyses reported that longer TL was associated with better general cognition 12 and performance in several cognitive domains. 13,14 Few population-based studies have explored TL in relation to brain MRI imaging features. [14][15][16] A recent meta-analysis showed that longer leukocyte TL is associated with whole brain and hippocampus volumes but not with white matter hyperintensities (WMH).…”
Section: Introductionmentioning
confidence: 99%